Remotely Maintaining and Modifying a Student-Run Tuberulosis Clinic During the COVID-19 Pandemic - Taylor Santoro; Alexandra Woodbridge; Sophie Foroushani; Andrew Crawford; Fiona Sylvies; Andrew Belnap; Rebekah Byrne; Juzar Ali (Journal of Student-Run Clinics, 2021)
The 2019 novel coronavirus pandemic challenged many aspects of the medical system, including student-run clinics. The Tulane University School of Medicine Tuberculosis (TB) Testing program offers risk evaluation and testing at six clinics in various facilities throughout New Orleans, Louisiana, and sees approximately 2,000 patients annually. Due to temporary removal of medical students from all clinical and volunteer activities, the program rose to the challenge to temporarily restructure operations in order to continue to provide resources and support at a time when physical contact was impossible. Medical student leaders took initiative in developing a TB screening questionnaire to be administered by non-medically trained essential facility staff, in addition to maintaining regular communication and providing off-site support. Although challenging, circumstance necessitated a temporary modification of student-run clinic models of care in order to protect safety and well-being of both students and the vulnerable populations served by the clinics. Anticipated repercussions from this temporary clinic model include rebound strains on clinic capacity at the time of reopening, in addition to a nationwide dearth of medical resources. However, the proactive response and flexibility of the student-run TB clinics will assure that this important aspect of care does not suffer needlessly during a time when all focus is on the pandemic.